FAHR’S DISEASE IN A PATIENT PRESENTING WITH STATUS EPILEPTICUS - Khalid, Shah; Khan, Shahbaz Ali; Khan, Abdul Hameed; Muhammad, Gul; Khan, Ahsan Aurnagzeb (Journal of Ayub Medical College Abbottabad, 2020)
Fahr’s disease is a rare disease in which there is symmetrical bilateral intracranial calcification. We are presenting a 50-year-old female patient who presented with status epilepticus. She had history of generalized tonic clonic fits for the last fifteen years. Her CT scan revealed widespread bilateral and symmetrical intracranial calcification in cerebellum, thalamus, basal ganglia and in white matter of the cerebral hemisphere Most of the secondary causes were ruled out to make the clinical diagnosis of Fahr’s disease. Keywords: Fahr’s disease, Fahr’s Syndrome; Intracranial Calcifications; Status Epilepticus; Seizures; Striopallido dentate calcinosis